PENGARUH DAYA TARIK IKLAN, PERSEPSI HARGA, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN DI E-COMMERCE TIKTOK SHOP (STUDI KASUS MAHASISWA UNTAG SURABAYA) - Dita Surya Elsani; Ida Aju Brahma Ratih (Nirta Akuntabel : The Indonesian Journal Of Economic and Accounting, 2025)
The development of digital technology is driving a shift in consumer shopping behavior from conventional markets to social media-based e-commerce. TikTok Shop exists as a platform that integrates video content, live streaming, and direct purchasing features, making visual advertising, price perception, and brand image important factors in influencing purchasing decisions. This study aims to analyze the influence of advertising appeal, price perception, and brand image on purchasing decisions of students at the University of August 17, 1945 Surabaya on the TikTok Shop e-commerce platform. The study used a quantitative approach with a sample of 98 Management students selected using the Lemeshow technique. Data were collected using a Likert scale questionnaire and analyzed using validity and reliability tests, multiple linear regression, t-tests, and F-tests. The results showed that all instruments were valid and reliable, with a Cronbach's Alpha value >0.6. Partially, advertising appeal, price perception, and brand image had a positive and significant effect on purchasing decisions with a significance value <0.05. Simultaneously, all three variables also had a significant effect on purchasing decisions with an F-value of 23.111 and a significance value of 0.000. This study concluded that an attractive advertising strategy, perceived appropriate prices, and a positive brand image can increase consumer purchasing decisions in TikTok Shop.